Description of Total Protein Levels in Pregnant Women at the Tambelan Sampit Health Center, Pontianak - Matius Sunti; Sutriswanto Sutriswanto; Emilda Sari (MEDICA (International Medical Scientific Journal), 2024)
Pregnancy is a critical period characterized by the growth and development of the fetus, during which the nutritional needs of the mother, including total protein intake, increase significantly. Total protein in the blood comprises albumin, globulin, and small amounts of other proteins, all essential for maternal and fetal health. This descriptive-analytic study aimed to determine the total protein levels in pregnant women attending the Tambelan Sampit Health Center. The study involved 30 pregnant women, including 9 in the first trimester, 10 in the second trimester, and 11 in the third trimester. Data were collected without generalization analysis to describe the condition of the study population. The highest total protein levels were observed in the first trimester (8.2 g/dL), followed by the third trimester (7.3 g/dL), and the second trimester (7.1 g/dL). In the first trimester, 55.6% of participants had normal protein levels, and 44.4% had abnormal levels. In the second trimester, 80% had normal levels, and 20% had abnormal levels. In the third trimester, 81.9% showed normal levels, and 18.1% had abnormal levels. It can be concluded that most of the pregnant women in this study had total protein levels within the normal range across all trimesters. Further research is recommended to conduct a more in-depth investigation of total protein levels during pregnancy.